A Critical Study of Grievances of Victims In India: Exploring the Evolution and Implementation of Victim's Compensation (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Victim’s compensation has always been the weepingbeggar at the door of criminal justice. Although, it is an age old concept butits development on more scientific lines and also as branch of criminology hasbegun since a few decades ago. Several countries have taken up the differentschemes of payment of compensation to their victims of crime. These are takenthrough different legislative measures.